Litter quality as driving factor for plant nutrition via grazing of protozoa on soil microorganisms. Issue 2 (11th April 2013) - Koller, Robert; Robin, Christophe; Bonkowski, Michael; Ruess, Liliane; Scheu, Stefan
Abstract: Plant residues provide a major source of nitrogen (N) for plant growth. Litter N mineralization varies with litter carbon‐to‐nitrogen (C‐to‐N) ratio and presence of bacterial‐feeding fauna. We assessed the effect of amoebae, major bacterial feeders in soil, on mineralization of litter of low (high quality) and high C‐to‐N ratio (low quality) and evaluated consequences for plant growth. We used stable isotopes to determine plant N uptake from litter and plant C partitioning. Stable isotope probing of phospholipid fatty acids was used to follow incorporation of plant C into microorganisms. Amoebae increased plant N uptake independent of litter quality and thereby the biomass of shoots and roots by 33% and 66%, respectively. Plant allocation of total 13 C to roots in low (42%) exceeded that of high‐quality litter treatments (26%). Amoebae increased plant allocation of 13 C to roots by 37%. Microbial community structure and incorporation of 13 C into PLFAs varied significantly with litter quality and in the low‐quality litter treatment also with the presence of amoebae. Overall, the results suggest that in particular at low nutrient conditions, root‐derived C fosters the mobilization of bacterial N by protozoa, thereby increasing plant growth when microorganisms and plants compete for nutrients.